Contribuições do design estratégico na identificação de cenários para a indústria fonográfica - Boeira, Juan Pablo Dávila (Universidade do Vale do Rio dos Sinos, 2014)
In markets where the need for a gaze directed toward the resolution of complex problems and the search for innovative solutions is growing, Strategic Design stands out as an aggregator function, form and symbol to the value of the product, service, communication and experience. In this context, it is possible to connect through the lens of Strategic Design, the small details to an holistic vision and understand the connection between the Design and the execution of a project, making it become a potential resource before the present context marketing. In this regard, the research in question aims to analyze the contributions of Strategic Design for the identification of scenarios for the phonographic industry. The research has a theoretical basis that underlies the study, the understanding of the environment experienced and the application of Strategic Design through exploratory research evaluating ways to identify the levels of understanding of the actors involved and the most productive moments in regard to the resolution of the problem proposed. Finally, we try to understand the importance of adapting the Design tools to the analyzed environment.
Keywords: Design estratégico; Indústria fonográfica e cenários; Strategic design; Phonographic industry and scenarios; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial